Implementasi Kebijakan Kartu Pedagang Produktif (KPP) di Kabupaten Bojonegoro - Syadwina Daniar; Rosyidatuzzahro Anisyukurlillah; Endik Hidayat (Jurnal Ilmu Sosial dan Ilmu Politik)
One of the main problems of Micro, Small and Medium Enterprises (MSMEs) in Bojonegoro Regency is limited capital and high loan interest rates. So, there is a need for a program to help MSME players. The Productive Trader Card (KPP) is a flagship program from Bojonegoro Regency designed to support and develop MSMEs. This research aims to find out how the implementation of the Productive Trader Card (KPP) policy at the Bojonegoro Regency Trade, Cooperatives and Micro Business Office. This research uses qualitative research methods with descriptive research type. The theory used is the theory of policy implementation from Van Meter and Van Horn, with six indicators, namely policy objectives and standards, policy resources, inter-organizational relations, implementer characteristics, political environment, socio-economic, and attitudes of implementers. The result of this study is that the implementation of the Productive Trader Card (KPP) policy can be said to be successful because all indicators have been well implemented, but there are still shortcomings, namely the discovery of policy resource indicators, especially human resources and indicators of implementer characteristics in the implementation of the Productive Trader Card (KPP) policy which are still not running optimally